PENUBUHAN PARTI POLITIK MENURUT PANDANGAN ISLAM - Thaib, Lukman (Jurnal Syariah, 2019)
As far as the establishment of political parties in Islam is concerned, the article attemps to trace back in the early history of Muslim the emergence of political parties, namely al-Khawarij, Shi’ah, Mu’tazilah and others. Based on historical background, the author tries to determine whether Islam in the modem age allow the establishment of political parties or not? Then it in any way tries to answer this question by referring to contemporary scholars as well as his own justification.